Sistem Monitoring Kualitas Air Secara Real Time pada Tambak Udang Vaname (Litopenaeus vannamei) - Muhammad Rizaldy; Alauddin Y; Muhammad Basri (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2026)
The continuous activity of Vanname shrimp farming can lead to environmental degradation, marked by a decline in water quality. The location of the pond must be close to a water source that has good quality and is free from pollution. This research aims to create a design tool for the water quality of shrimp ponds. The design for the water quality of Vannamei shrimp ponds forms the basis of the qualitative research method, which draws from relevant literature. Using the Visual Studio programming language. The implementation of the research was conducted at a shrimp farm location in the city of Parepare. The results of the prototype design and construction can monitor pH values ranging from the lowest to the highest, which are 7.06–8.13, and salinity values from 15710–4905 ppm. Through the application, the water quality in the pond is monitored as normal, with a pH of 7.5–8.5 and salinity of 15–25 ppt. The device that has been created is functioning well.